Synthesis Of Monolayer Graphene On Polycrystalline Nickel And Nickel-Copper Bimetallic Catalyst And Study Toward The Reuse Of Nickel Catalyst - Seah, Choon Ming (2016)
Graphene is a layer of sp2 hybridized carbon atoms with a thickness of only one atom, which exposed most of its atoms to the surrounding medium. Since the discovery of graphene in 2004, it has become the main subject of research around the world. The attractiveness of graphene is mainly attributed to its remarkable mechanical, optical, thermal and electrical properties, enabling graphene to be potentially used in various applications. To date, CVD is the promising method to produce wafer-scale graphene, because it allows an easier separation of graphene from the catalytic substrate. With the assist of fast cooling, monolayer graphene was grown directly on polycrystalline Ni foil under atmospheric pressure CVD with temperature of 850 ºC, methane partial pressure of 0.2 atm and reaction duration of 5 min. However, monolayer graphene could not be formed on Cu under the chosen CVD conditions. Fast cooling after CVD allowed the quenching of the activity of the catalyst and limiting diffusion of dissolved carbon to the surface of Ni, which later facilitate the formation of predominantly wafer scale monolayer graphene. To further improve the uniformity of monolayer graphene, a facile technique was applied to grow monolayer graphene simultaneously on both polycrystalline Ni and Cu foils using a Ni-Cu bilayer catalyst at temperature of 950 ºC, methane partial pressure of 0.2 atm and reaction duration of 5 min. High uniformity and quality of the crystalline structure of the grown graphene was evidenced by Raman spectroscopy mapping and High Resolution Transmission Electron Microscope. The straightforward bimetallic catalytic system allows the control of carbon diffusion to the interface of Ni and Cu. In particular, carbon accessibility is reduced at the inner Ni surface, and Cu behaves as a carbon barrier. The growth mechanism of monolayer graphene was facilitated by carbon diffusion through the bulk and Ni grain boundary, the driving force coming from concentration gradient between carbon-rich surface to carbon-lacked surface. The grain boundaries were shown to play a crucial role in carbon control during the growth stage. Facilitated by the applied fast cooling, the quenching process reduced the amount of carbon atoms segregated, only the carbon atoms situated near the surface had enough time to segregate and form graphene. Meanwhile, diffusion of carbon atoms at the middle of the Ni foil was highly inhibited; forming Ni3C. Ni3C is known to offer good protection against corrosion. The presence of Ni3C combined with the use of iron nitrate (0.5mol/L) as soft etchant for graphene separation, the Ni foil could be reused again up to 6 cycles without causing a huge deviation on the quality and the uniformity of bilayer graphene. Ni3C is indeed able to limit the etching effect of the Ni foil. This work has successfully demonstrated a simple and novel route to synthesize monolayer graphene with high quality.